2020
DOI: 10.1016/j.crfs.2019.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

Improved bioaccessibility of polymethoxyflavones loaded into high internal phase emulsions stabilized by biopolymeric complexes: A dynamic digestion study via TNO's gastrointestinal model

Abstract: In this work, the bioaccessibility of polymethoxyflavones (PMFs) loaded in high internal phase emulsions (HIPE, ϕ oil = 0.82) stabilized by whey protein isolate (WPI)-low methoxy pectin (LMP) complexes was evaluated using in vitro lipolysis and dynamic in vitro intestinal digestion studies. PMFs loaded HIPE was prepared by using aqueous dispersion of pre-formed biopolymeric complexes (WPI-LMP, 2:1 ratio) as the external phase and medium chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The bioaccessibility of 5-DN was found to be higher (18.3%) with emulsion than in bulk oil (9.2%). Similar results were found by Wijaya et al [62]. 1.5-and a 2-fold increase in the bioaccessibility of nobiletin was obtained within HIPE-complexes compared to within bulk oil after in vitro lipolysis and the gastrointestinal model TIM-1 digestion, respectively.…”
Section: Improving the Bioaccessibility Of Phenolic Compounds By Meansupporting
confidence: 89%
See 1 more Smart Citation
“…The bioaccessibility of 5-DN was found to be higher (18.3%) with emulsion than in bulk oil (9.2%). Similar results were found by Wijaya et al [62]. 1.5-and a 2-fold increase in the bioaccessibility of nobiletin was obtained within HIPE-complexes compared to within bulk oil after in vitro lipolysis and the gastrointestinal model TIM-1 digestion, respectively.…”
Section: Improving the Bioaccessibility Of Phenolic Compounds By Meansupporting
confidence: 89%
“…Besides, according to the dynamic in vitro gastrointestinal model (TIM-1) results, the bioaccessibility of tangeretin increased 2.6-fold when it was incorporated into the viscoelastic system rather than in the oil suspension [61]. Similarly, a recent study [62] compared the effects of high internal phase emulsions (HIPE) stabilized by whey protein isolate-low methoxy pectin complexes and medium chain triglyceride (MCT) oil as a suspension on the bioaccessibility of tangeretin using in vitro lipolysis and dynamic in vitro intestinal digestion studies. The in vitro lipolysis results revealed that the bioaccessibility of tangeretin in HIPE-complexes was increased 2-fold compared to that of the bulk oil.…”
Section: Improving the Bioaccessibility Of Phenolic Compounds By Meanmentioning
confidence: 85%
“…Similarly, β-carotene encapsulated within whey protein-stabilized HIPEs had a considerably higher bioaccessibility (36%) than that dispersed in bulk oil (13%) [78]. The encapsulation of various other hydrophobic bioactive substances in HIPEs has also been shown to appreciably enhance their bioaccessibility, including curcumin [55,79], lutein [80], polymethoxyflavones [81,82], and resveratrol [83]. The increase in nutraceutical bioaccessibility after encapsulated in HIPEs has been attributed to a number of mechanisms: (i) the gel network in HIPEs reduces the aggregation of the oil droplets during digestion, thereby increasing the access of lipase to the lipid droplets and increasing their digestion; (ii) the bioactive compounds trapped inside the oil droplets are protected from degradation within the gastrointestinal tract; and (iii) the high levels of lipids present in HIPEs lead to the formation of a large number of mixed micelles, capable of solubilizing the carotenoids [84].…”
Section: High Internal Phase Emulsionsmentioning
confidence: 99%
“…The blank emulsions had no significant changes in their particle size after gastric digestion, probably as the viscosity of the continuous phase made the action of lipase difficult. As suggested by Wijaya et al [ 32 ], polysaccharides like pectin can form an interpolymeric gel network around the emulsion droplets due to electrostatic interactions that are not easily displaced. However, in the presence of AP and AS extracts weaker interpolymeric gel networks might be formed due to the occurrence of non-covalent complexes between pectin and the phenolic species from these extracts.…”
Section: Resultsmentioning
confidence: 99%